Differences Between Blood Glucose Testing Using POCT and Photometer Methods at STIKESMAS Abdi Nusa Palembang - Warsinah Warsinah; Juwy Trianes; Dedek Sesar Azzuhra (Jurnal Altifani Penelitian dan Pengabdian kepada Masyarakat, 2026)
Blood glucose is the body's main source of energy derived from carbohydrate metabolism, and its examination is important for monitoring and diagnosis, especially in critical conditions. Glucose testing can be performed using Point of Care Testing (POCT) or a photometer. This study aims to determine the differences in blood glucose test results using these two devices. The study employed a cross-sectional design involving 31 fifth-semester students from STIKESMAS Abdi Nusa through total sampling. Blood glucose testing was performed using glass blood samples for POCT and venous blood serum samples for photometers. Data analysis used the Kolmogorov–Smirnov test and independent t-test. The results of the analysis showed a p-value of 0.29 (>0.05), which means that there was no significant difference between the blood glucose test results using POCT and photometers. These findings indicate that POCT can be used as a tool for monitoring and screening blood glucose, while photometers remain the primary reference for diagnosis. Further research is recommended to compare different devices or use a larger sample size to increase the strength of the analysis.